EXERGY ANALYSIS OF A COMBUSTOR - Amirul Affannuhafiz Abdul Muttaleb; Mohd Rosdzimin Abdul Rahman; Mohd Rashdan Saad; Mohd Faizal Hasan; Kahar Osman; Ishkrizat Taib (Applications of Computational Fluid Dynamics in Mechanical Engineering (Series 4), 2025)
This study presents an exergy analysis of a premixed hydrogen/air miniature combustor, focusing on the impact of different bluff body ratios on combustion characteristics and exergy performance. The primary objective was to investigate the combustion efficiency and stability at varying bluff body geometries and inlet velocities, with an emphasis on improving energy conversion. The results show that the bluff body ratio of 0.3 provided the best overall combustion performance, with stable flame development and efficient energy conversion at inlet velocities between 10 m/s and 12 m/s. Higher velocities, specifically at 14 m/s, led to decreased flame stability and reduced exergy efficiency due to poor mixing and potential cooling effects. The exergy efficiency peaked at velocities around 10 m/s, demonstrating the system's ability to effectively convert energy into useful work while minimizing energy loss. This analysis contributes to the development of more efficient combustion systems, offering insights into optimal design parameters for sustainable energy use. The findings support the achievement of the United Nations Sustainable Development Goal (SDG) 7, "Affordable and Clean Energy," by advancing the design of miniature combustors with improved energy efficiency. Keywords: Heat transfer, CFD, combustion, bluff body